Civil law status of virtual world objects (Eurasian Research Bulletin, 2023)
The article analyzes the problems of determining the legal status of the virtual world and objects in it, examines the theory of virtual property and gives the relationship between property and intellectual property rights to regulate relations arising in the virtual world. The author, on the basis of the analysis carried out, puts forward a proposal on the need to regulate relations in the field of creating computer codes to gain access to the virtual world using intellectual property norms, since the creative work of a person is involved, and to use the norms of property rights in relations of ownership of objects of the virtual world - domain names, URLs (uniform resource locators), websites, email accounts, crypto assets, items (artifacts and enhancements) in online multiplayer games. The author is developing a proposal on the need to supplement the current Civil Code of the Republic of Uzbekistan with a category of virtual property, which certifies the owner's right in relation to the objects of the virtual world. The author studies the theoretical statements of legal scholars regarding the status of virtual property, and comes to the conclusion that relations in the virtual space should be regulated by the norms of intellectual property and property law, while both institutions should not compete and mutually exclude each other, but, on the contrary, regulate in virtual space relationships based on their essence